Dopamine alters phage morphology to exert an anti-infection effect - Hu, Xiuling; Zhang, Chunting; Ju, Yani; Liu, Xin; Zhang, Shengting; Wei, Yunlin (Frontiers in Microbiology, 2023)
Antiviral drug development is important for human health, and the emergence of novel COVID-19 variants has seriously affected human lives and safety. A bacteriophage-a bacterial virus with a small and simple structure-is an ideal experimental candidate for studying the interactions between viruses and their hosts. In this study, the effects and mechanisms of catecholamines on phages were explored, and dopamine (DA) was found to have general and efficient anti-infection effects. A clear dose-dependent effect was observed when different phages were treated with DA, with higher DA concentrations exhibiting stronger anti-phage activity. The half maximal inhibitory concentration values of DA for vB-EcoS-IME167, T4 Phage, and VMY22 were determined as 0.26, 0.12, and 0.73 mg mL -1 , respectively. The anti-phage effect of DA increased with treatment duration. In addition, the anti-infection activities of DA against vB-EcoS-IME167, T4 Phage, and VMY22 were increased by 10 5 , 10 4 , and 10 4 folds compared to that of the control. This ability of DA was observed only in phages and not in the host bacteria. Morphological changes of phages were observed under transmission electron microscopy following their treatment with DA, and considerable changes in adsorption were confirmed via quantitative reverse transcription polymerase chain reaction. These results suggest that the anti-phage effect of DA is primarily due to the destruction of the external structure of the phage. This study, to the best of our knowledge, is the first to report the universal anti-phage infection effect of dopamine, which provides novel information regarding DA and forms a basis for further research and development of antiviral drugs. Moreover, it provides a new perspective for the research about the defense and counter-defense of bacteria and bacteriophages.